2006
DOI: 10.1007/s00213-006-0529-6
|View full text |Cite
|
Sign up to set email alerts
|

Toward a model of drug relapse: an assessment of the validity of the reinstatement procedure

Abstract: We find that the reinstatement model has adequate criterion validity in the broad sense of the term, as evidenced by the fact that reinstatement in laboratory animals is induced by conditions reported to provoke relapse in humans. The model's criterion validity in the narrower sense, as a medication screen, seems promising for relapse to heroin, nicotine, and alcohol. For relapse to cocaine, criterion validity has not yet been established primarily because clinical studies have examined medication's effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
478
2
15

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 585 publications
(505 citation statements)
references
References 195 publications
(182 reference statements)
10
478
2
15
Order By: Relevance
“…The role of the kappa opioid receptor in stress-and cocaine-priming-induced reinstatement Stress exposure has been found to potentiate addictive drug related behaviors (for example Covington and Miczek 2005;McLaughlin et al 2003McLaughlin et al , 2006a, and stress is a major precipitating factor for relapse of drug seeking (Epstein et al 2006;Stewart 2003). The principal findings of the present study were that reinstatement of cocaine seeking by stress exposure, but not by cocaine priming, was kappa-opioid-receptor-mediated.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The role of the kappa opioid receptor in stress-and cocaine-priming-induced reinstatement Stress exposure has been found to potentiate addictive drug related behaviors (for example Covington and Miczek 2005;McLaughlin et al 2003McLaughlin et al , 2006a, and stress is a major precipitating factor for relapse of drug seeking (Epstein et al 2006;Stewart 2003). The principal findings of the present study were that reinstatement of cocaine seeking by stress exposure, but not by cocaine priming, was kappa-opioid-receptor-mediated.…”
Section: Discussionmentioning
confidence: 49%
“…Towards this goal, animal models of relapse were developed that identified triggers for reinstatement of drug selfadministration Stewart 1981, 1983;Gerber and Stretch 1975;Stretch and Gerber 1973). Drug reinstatement studies have shown that presentation of drug-associated cues, drug priming, and acute footshock stress each increased drug self-administration (see Bossert et al 2005;Epstein et al 2006;Shaham et al 2003). While the direct extension from animal models of reinstatement to human addiction experience may be problematic (Katz and Higgins 2003), a relationship between stress and drug addiction has been repeatedly noted (see Koob 2006), and treatments that enhance stress resilience might reduce the frequency of relapse.…”
Section: Introductionmentioning
confidence: 99%
“…For example, sign-tracking CR performance of alcohol drinking in rats is virtually unchanged following a 27-day retention interval (Tomie et al, 2002c) or following a 41-day retention interval (Tomie et al, 2004a). Maintenance of sign-tracking CR performance of sipper CSdirected alcohol drinking over time, without appreciable decay or deterioration in the performance, is similar to relapse in humans and reinstatement of drug-taking in animals (Kruzich et al, 2001;Stewart, 2004; for review of reinstatement as a model of relapse, see Epstein et al, 2006;Fattore et al, 2007). In each of these cases there is little evidence of loss of responding during the retention interval, even though responding is not practiced during this extended period of time.…”
Section: Relapse-like Effectsmentioning
confidence: 99%
“…In this study, we used a rat model of relapse to heroin seeking (Epstein et al, 2006), in which animals selfadminister heroin in the presence of compound cues (Van den Oever et al, 2008). We show that heroin selfadministration leads to long-term changes in synaptic levels of ECM constituents in the mPFC.…”
Section: Introductionmentioning
confidence: 99%